Green product and green marketing as determinants of brand image and consumer purchase decision in the packaged tea industry - Farida, Siska Nifro'atul; Santoso, Imam; Mustaniroh, Siti Asmaul; Wafi'uddin, Izzum (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Growing environmental concerns have prompted companies, including those in the packaged tea industry, to adopt green strategies. However, the extent to which these strategies actually influence consumer perceptions and purchasing decisions remains a crucial area for investigation. This study aimed to analyse the influence of green products and green marketing on brand image and consumer purchasing decisions for tea packaged in Returnable Glass Bottling (RGB) in Malang City. This study uses a quantitative approach by collecting data from 160 respondents selected through purposive sampling. The data were analysed using the Partial Least Square (PLS) method. The goodness of fit test results showed that the model has good feasibility with a value of 0.545. The main findings indicated that green products and green marketing positively and significantly influenced brand image and purchasing decisions. Furthermore, brand image also significantly influenced purchasing decisions and was proven to be a strong mediator in the relationship between green strategies (products and marketing) and purchasing decisions. This study confirmed the implementation of effective green strategies can build a positive brand image, which in turn significantly encouraged consumer purchasing decisions in the packaged tea industry.